Penerapan Absensi yang Berbasis Teknologi Digital dengan Perangkat Mesin di PT. Sabda Sentosa - Yonson Pane; Frengky Situmorang (Outline Publisher, 2023)
This community service activity aims to provide understanding and changes in manual work methods to technology-based work methods, in this case the application of a digitalized attendance system. employees and workers alike. Manual attendance system at PT. Sabda Sentosa has various problems that have occurred and have been discussed in the previous chapter. One of the problems that often arises is the difficulty of determining the wages of these workers, where the attendance record of the workers is not present, but the workers are present and vice versa.